Ensuring Support for Research and Quality Improvement (QI) Networks: Four Pillars of Sustainability—An Emerging Framework - Holve, Erin (EGEMS (Wash DC), 2013)
Multi-institutional research and quality improvement (QI) projects using electronic clinical data (ECD) hold great promise for improving quality of care and patient outcomes but typically require significant infrastructure investments both to initiate and maintain the project over its duration. Consequently, it is important for these projects to think holistically about sustainability to ensure their long-term success. Four “pillars” of sustainability are discussed based on the experiences of EDM Forum grantees and other research and QI networks. These include trust and value, governance, management, and financial and administrative support. Two “foundational considerations,” adaptive capacity and policy levers, are also discussed.